Regeneration of elastic cartilage with accurate human-ear shape based on PCL strengthened biodegradable scaffold and expanded microtia chondrocytes. (September 2020) - Yin, Zongqi; Li, Dan; Liu, Yi; Feng, Shaoqing; Yao, Lin; Liang, Xiaoqin; Miao, Chunlei; Xu, Yong; Hou, Mengjie; Zhang, Ruhong; Zhang, Wenjie; Liu, Wei; et al.
Highlights: The current study successfully regenerated human-ear-shaped cartilage using PGA/PLA-PCL scaffolds and human MCs. The PCL support presented good biocompatibility and had no negative effect on cartilage regeneration with satisfactory tissue integration. The PCL support significantly improved mechanical strength and shape maintenance of the engineered cartilage. The regenerated cartilage presented mature elastic cartilage phenotype after long-term implantation. The implanted MCs could survive for a long time and maintain their phenotype in regenerated cartilage after implantation. Abstract: Tissue engineering provides a promising approach for auricle reconstruction of microtia. Although the first clinical trial of tissue-engineered ear reconstruction has been performed using in vitro engineered human-ear-shaped cartilage, this approach is not regarded as the clinically available treatment yet, due to individual differences in clinical efficacy. In the present study, the feasibility and in vivo long-term fate of elastic cartilage regenerated with an accurate human-ear shape were explored using polycaprolactone (PCL) inner support strengthened biodegradable scaffold and expanded microtia chondrocytes (MCs) to identify factors that may result in discrepant clinical outcomes. Polyglycolic acid/polylactic acid (PGA/PLA) scaffolds with or without PCL inner support were prepared into different shapes by three-dimensional (3D) printing, hot-compressing, and pre-molding technologies. The expanded MCs were seeded into the scaffolds to evaluate biocompatibility of PCL inner support and its influence on cartilage regeneration, tissue integration, mechanical strength, and shape maintenance. The results testified that all the cartilages generated by different patients' cells were highly consistent in both qualitative and quantitative data, indicating high repeatability and stability of cartilage construction technology. PCL inner support manifested a satisfactory biocompatibility and it had no inhibitory effect on cartilage formation, maturation, and tissue integration. After in vivo implantation, the regenerated cartilage without PCL inner support showed the same level of mechanical strength and shape maintenance ability as the PCL strengthened cartilage. Mature and continuous elastic cartilage with an accurate ear shape could be successfully regenerated in vivo with a long-term shape maintenance. All the cells of regenerated cartilage were derived from the implanted MCs, which could survive and maintain their phenotype for a long time. The current study provides reliable evidence, key techniques, and optimized strategies for further clinical applications of in vitro regenerated cartilage with special shapes such as ear, nose, and trachea. Graphical abstract: Image, graphical abstract